102 The impact of gender and marital status on long term mortality in patients with cardiovascular disease: insights utilising big data from the ACALM study. (May 2019) - Potluri, Rahul; Qashou, Ahmed; Carter, Paul; Patel, Billal; More, Ranjit; Lavu, Deepthi
Abstract : Background: Married patients with Acute Coronary Syndrome (ACS) have significantly improved mortality compared to single patients while the worst outcomes are seen among divorcees. The impact of gender, marital status and outcomes in patients with cardiovascular disease has been poorly studied. Using big data, we addressed this further by studying patients with ACS, Heart Failure (HF) and Atrial Fibrillation (AF). Methods: Anonymous information on patients with ACS, HF and AF, including comorbidities, was obtained from UK hospitals between 1st January 2000 and 31st July 2014. This data was amalgamated according to the Algorithm for Comorbidities, Associations, Length of stay and Mortality (ACALM) study protocol using ICD-10 and OPCS-4 coding. Long term mortality analysis was performed using cox regression adjusting for demographics, comorbidities and Charlson Comorbidity Index. Results: Of 1, 816, 230 patients, there were 28, 699 ACS, 36, 719 HF and 52, 812 AF patients with marital status. ACS was more common in males (64%) but an even split was seen in HF and AF. Males with ACS, HF and HF were significantly younger than females. Cox regression showed that married (OR0.77) or widowed (OR0.76) patients had lower long term mortality than single or divorced patients with ACS. Among those with HF and AF, married (OR0.70 HF; OR0.68 AF) and widowed patients (OR0.71 HF;OR0.69 AF) had significantly better mortality compared to singles. Divorcees had the worst mortality (OR1.31 HF;OR1.26 AF). As shown in table 1 and figure 1, widowed females had lower mortality compared with widowed males in the ACS, HF and AF groups. Interestingly, single males with HF had lower mortality compared to single females. In the AF group, married and divorced females had lower mortality than married and divorced males respectively. Conclusion: Understanding gender differences in marital status will further our understanding of the complex role of the support mechanisms that are required to best manage patients with ACS, HF and AF. Targeting patients with the worst outcomes with a greater focus on holistic care could lead to improved prognosis. Conflict of Interest: Nil